Analisis Penggunaan Model Pembelajaran Inquiry Kelas IV di SDN Petir 4 - Nicken Novita Sari; Azmy Hadisa; Virania Ananda (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2020)
This study aims to determine: 1) Learning models use in science subject 2) Constrains in the use of learning models 3) Student learning outcomes in the inquiry learning models 4) Student responses is the use of inquiry learning models 5) Effort to overcome obstaceles in the use of learning models to achieve specified learning objectives. This research was conducted with the 4th grade homeroom teacher with interview techniques. From the result of the interview can be obtained that 1) Learning models use in science subjects in Petir 4 Elementary School are inquiry learning models 2) The obstacles faced in using this learning model are lack of adequate teaching aids differences in the characteristic of different students who are slow in accepting and understanding the information conveyed 3) Student learning out cones inquiry learning depends on the learning media and learning method in thematic learning more children who are active in the classroom, while the teacher only prevides further information the children who complete, of course different from KTSP. In KTSP teachers are more active than students grade four 4) Student responses in use of inquiry learning model that is good response, if the teacher is active his child also actively follows the teacher, whereas if the child is left in the classroom are not condutive 5) Effort to overcome obstacles in the use of inquiry learning models, namely by providing motivation and adding props to make it more interesting when learning takes place.